Designing large-scale antenna array using sub-array - Mukit, Naimul; Islam, Md Rafiqul; Alam, A H M Zahirul; Abdullah, Khaizuran; Abdul Malek, Norun Farihah; Nibir, Rauful; M Adnan, Noor Hidayah; Osman, Eid (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Ahmad Dahlan, 2019)
Antenna array of large scale have been examined for different applications including 5G technology. To get better data rate or a reliable link substantial number of antenna arrays have been utilized to provide high multiplexing gains as well as array gains with high directivity. In this paper a simple but efficient implementation technique of using sub-arrays for the improvement of large-sized uniform arrays. By repeating a small sub-array multiple times large arrays can be designed. This implication of utilizing small array simplifies the design of a larger array which allows the designer to concentrate on the smaller sub-array before assembling larger arrays. So, by investigating the sub arrays the performance and radiation characteristics of large arrays can be anticipated. The array-factor for a planar sub-array of 2x2 (4 elements) is analyzed using Mat-lab software and then a large array is formed by placing the 2x2 sub-array in different configurations in a rectangular arrangements up to 8x8 planar array. And then the results are validated with CST (Computer simulation technology) simulation results. In this way the array-factors, directivities, HPBWs, and side lobes of the constructed large arrays are analyzed and associated with the small sub-array.